Erlotinib resistance in mouse models of epidermal growth factor receptor-induced lung adenocarcinoma - Politi, Katerina (The Company of Biologists Limited, 2010)
Seventy-five percent of lung adenocarcinomas with epidermal growth factor receptor (EGFR) mutations respond to treatment with the tyrosine kinase inhibitors (TKIs) gefitinib and erlotinib; however, drug-resistant tumors eventually emerge. In 60% of cases, resistant tumors carry a secondary mutation in EGFR (T790M), amplification of MET, or both. Here, we describe the establishment of erlotinib resistance in lung tumors, which were induced by mutant EGFR, in transgenic mice after multiple cycles of drug treatment; we detect the T790M mutation in five out of 24 tumors or Met amplification in one out of 11 tumors in these mice. This preclinical mouse model, therefore, recapitulates the molecular changes responsible for resistance to TKIs in human tumors and holds promise for the discovery of additional mechanisms of drug resistance in lung cancer.